Fertility Choice and Economic Growth: Theory and Evidence - Wang, Ping; Yip, Chong K.; Scotese, Carol A. (The Review of Economics and Statistics, 1994)
This proposed theoretical model is based on new models of Barro and Becker and Becker Murphy and Tamura and explains the interaction of family decisions about fertility and the macroeconomy in a growth situation. The proposed model captures a dynamic interaction between labor/leisure and fertility choice and a structural fertility preference shock. Endogenous factor are consumption labor/leisure and fertility while exogenous factors are production and utility parameters. The aim was to develop a general equilibrium model which expresses short- and long-term dynamics to test the impact of economic disturbances on fertility and to explain the US baby boom and subsequent fertility patterns. Savings in capital accumulation and in labor supply were expected to have ambiguous effects while improved productivity was expected to increase steady state consumption. The methodology a structural Vector Auto Regression (VAR) model was developed by Blanchard and Quah and Ihmed Ickes Wang and Yoo. Structural impacts include disturbances in employment fertility (theoretical preference shift) and output. Long-term restrictions are based on theory rather than on ad hoc causal orderings (Sims method) or current responses (Bernanke method). The structural VAR model is estimated using the logged differences of labor fertility rate and output. The empirical results are based on analysis of US data (1949-88) on fertility weekly hours worked and real gross national product. The model revealed that fertility choice should not be considered exogenous to the labor market or to economic growth. Variance of the forecast error for the fertility rate was significantly explained by employment shocks; the effect was reduced fertility and increased labor force effort. Output responses to fertility and technology shocks were similar to those reported by Shapiro and Watson. In the variance decomposition analysis output shocks explained about 33% of output variance. Fertility shocks explained about 33% of labor growth and 25% of output growth after the first year. With a lag of one year about 37% of fertility variance was explained by employment shocks. Concluding remarks underscore the importance of knowing which shock initiated the motion and causal ordering.